Structure formation in non-local bouncing models - Jackson, D. [UNESP]; Bufalo, R. (IOP Publishing, 2023)
In this study, we investigate the growth of structures within the Deser-Woodard nonlocal theory and extend it to various bouncing cosmology scenarios. Our findings show that the observable structure growth rate, fσ 8, in a vacuum-dominated universe is finite within the redshift range of 0 < z < 2, contrary to previous literature. Although fσ 8 exhibits no divergences, we observe a slight difference between the evolution of the ΛCDM and the non-local DW II models. Regarding structure formation in bouncing cosmologies, we evaluate the evolution of fσ 8 near the bouncing point. Among the different bouncing cases we explore, the oscillatory bounce and pre-inflationary asymmetrical bounce demonstrate a physical profile where the growth rate begins as a small perturbation in the early epoch and increases with inflation, which can be regarded as the seeds of large-scale structures. These findings are significant because they shed light on the growth of seed fluctuations into cosmic structures resulting from non-local effects.
Keywords: cosmic singularity; cosmological perturbation theory; Cosmological perturbation theory in GR and beyond; galaxy clusters